UNIGO - UNIMAS DIGITAL SUMMONS SYSTEM - JACKY, LEE NGAN KONG (Universiti Malaysia Sarawak, (UNIMAS), 2023)
UNIGO – UNIMAS Digital Summons System aims to provide a more efficient and convenient way for UNIMAS vehicle drivers to view and pay their summonses online. The app will also allow users to make complaints about illegal parking and view the status of their complaints. Additionally, the app empowers UNIMAS Ancillary Police (UAP) by enabling them to issue digital traffic summons for any traffic violation, ensuring streamlined enforcement and record-keeping processes. This comprehensive solution enhances transparency, accountability, and user convenience in managing traffic-related matters within the UNIMAS community. The app will be available for Android platforms. The main objective of this project is to develop an easy-to-use mobile application that streamlines the process of paying summonses and making complaints for illegal parking, reducing the burden between UNIMAS vehicle drivers and UAP, and making summons management more efficient. The app will be developed using the latest technologies such as Flutter for cross-platform development and Firebase for real-time data synchronization. These technologies will enable efficient development and seamless user experiences across different devices and platforms. User-friendly design principles will be implemented to ensure intuitive navigation, clear visual cues, and responsive interactions, enhancing the overall user experience of the app. This project is expected to provide significant benefits to UNIMAS vehicle drivers by reducing the time and effort required to pay summonses and make complaints, and by improving the overall parking management process at UNIMAS.